FTTH NETWORK DISTURBANCE ANALYSIS BASED ON ATTENUATION AND RECEPTION POWER ON THE INDIHOME SINGKAWANG NETWORK - Oktariani, Ade; Imansyah, Fitri; Yacoub, Redi Ratiandi (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2023)
Optical fiber is a transmission medium that allows it to meet human needs to be able to transfer data faster because it uses light as a conductor. There is a damping problem in optical fiber, it needs to be accommodated so as to minimize the occurrence of attenuation in optical fiber. With this research, it can be known the magnitude of the value of a fiber optic transmission attenuation through the method of measuring attenuation values and receiving power at the customer's home   using OPM, identifying fiber optic channel attenuation that affects the quality of internet services, and knowing the comparison of OPM measurement results with OT data reading. This study uses an analytical descriptive approach where the research will describe what it is about a variable that is processed, as well as the symptoms and conditions to be identified. So the results of the study can be obtained, namely, the amount of attenuation measured in the customer's home is influenced by the attenuation measured in ODP. Attenuation at ODP is small with an average optical power value of -18.39 dB, this makes attenuation in customers' homes, namely ONT, tend to be smaller with an average optical power value of -20.04 dB. There is an additional value   of -1.65   dB per transmission. So it is known that the longer the cable used for fiber optic transmission, the greater the attenuation produced so that the optical power emitted by the sender will weaken along with the length of the cable. This is what will affect the quality of internet services.